"Ściszyć" aktoreczkę. Słuchowisko "Andy" Krzysztofa Czeczota jako kryminał w dźwięku = "Turn down the actress". Krzysztof Czeczot's radio drama "Andy" as an audio-crime story - Łastowiecki, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A thriller does not have to be associated with a bloody knife, a victim?s body and a long coat of thedetective. The radio drama "Andy" uses the convention noir to show suggestively a media murder. The lethal weapon turns out to be a key on a computer keyboard, which successfully turns down thevolume of the voice of an actress, thus ending her life in television. The article demonstrates the roleof the listener in the formula of surround sound created by the author of the drama.
Keywords: Czeczot, Krzysztof (1979- ); słuchowisko radiowe